Gordon Craig and the mask of method: Robinson Crusoe and his pyre of a thousand ships (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
Edward Gordon Craig was fascinated by masks. He collected, catalogued, but also researched its expressive and pedagogical possibilities. In Craig, the mask went beyond its concrete meaning to become a mechanism for investigation and deepening his research. The creation of personas, hidden under pseudonyms, was part of this artifice of creating a polyphony of voices created by himself, so that each line of reasoning could be carried to the end. On this contradiction, Craig built his heterodox and revolutionary thought.Lonely and contradictory characters, like Hamlet, satisfied him most of all. But his encounter with Robinson Crusoe, by Daniel Defoe, was symbolic not only because it reflected his belief in the mythology of the man who builds a civilization with his own hands, but also in that of the shipwrecked man, abandoned in a desolate and dark environment, like that of second great war that was already announced.This study deals with what I called a masking methodology, and due to the solitary and civilizing nature that this methodology implies, I use as a basis for reflection Craig's project of illustrating with engravings a publication of the novel Robinson Crusoe, by Daniel Defoe. Craig identified with the loneliness of Crusoe and Hamlet, and with their ability, despite being alone, to be many.
Keywords: theater; Edward Gordon Craig; Robinson Crusoé; loneliness; mask